Identification of a Hemizygous Novel Splicing Variant in ATRX Gene: A Case Report and Literature Review - Yan Cong; Jie Wu; Hao Wang; Ke Wu; Cui Huang; Xuejian Yang (Frontiers Media S.A., 2022)
BackgroundAlpha-thalassemia/intellectual disability syndrome (ATR-X) (OMIM # 301040) was first described by Wilkie et al. (1). Several studies found that children who presented with significantly consistent clinical phenotypes of hemoglobin H (Hb H) disease and profound mental handicap carried ATRX chromatin remodeler (ATRX, OMIM*300032) gene variants. With the recent development of exome sequencing (ES), ATRX gene variants of severe to profound intellectual disability without alpha-thalassemia have been implicated in intellectual disability-hypotonic facies syndrome, X-linked, 1(MRXHF1, OMIM #309580). These two diseases present similar clinical manifestations and the same pattern of inheritance.Case PresentationWe reported a 3-year-old boy with intellectual disability, language impairment, hypotonia, and mild craniofacial abnormalities (flat nasal bridge, small and triangular nose, anteverted nostrils, and widely spaced incisors) and reviewed MRXHF1 cases. At an early stage, the patient developed global developmental delay (GDD). After 6 months of rehabilitation therapy, the patient's motor ability did not make big progress, as well as his speech or nonverbal communication. We performed whole-genome sequencing (WGS), Sanger sequencing, reverse transcription-polymerase chain reaction (RT-PCR), and X-inactivation studies. A novel hemizygous intronic variant in ATRX (c.5786+4A>G; NM_000489.6) was identified, which led to exon 24 skipping. The carrier mother showed extremely skewed X-chromosome inactivation (XCI). These results may contribute to the patient's phenotypes.ConclusionsThe novel hemizygous intronic variant in ATRX is the genetic etiology of the boy. Identification of this variant is helpful for parents to take prenatal diagnostic tests. Also, this new case expands the phenotypes of MRXHF1 and the mutational spectrum of the ATRX gene.